2019
DOI: 10.1186/s42234-019-0028-9
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive treatment of patients with upper extremity spasticity following stroke using paired trans-spinal and peripheral direct current stimulation

Abstract: Background: Muscle spasticity is a common impediment to motor recovery in patients with chronic stroke. Standard-of-care treatments such as botulinum toxin injections can temporarily relieve muscle stiffness and pain associated with spasticity, but often at the expense of increased muscle weakness. Recent preclinical investigations of a non-invasive treatment that pairs trans-spinal direct current stimulation and peripheral nerve direct current stimulation (tsDCS+pDCS) provided promising data for a novel appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 48 publications
(60 reference statements)
0
22
0
Order By: Relevance
“…Interestingly, patients did not receive any intervention and/or treatment during the trial duration, indicating that the observed clinical results were mostly associated to the intervention itself. The authors of this study used standardized spasticity measurements and stroke-specific, performance-based impairment index to assess improvement, thus, showing the applicability of this technique in the clinical setting (Paget-Blanc et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, patients did not receive any intervention and/or treatment during the trial duration, indicating that the observed clinical results were mostly associated to the intervention itself. The authors of this study used standardized spasticity measurements and stroke-specific, performance-based impairment index to assess improvement, thus, showing the applicability of this technique in the clinical setting (Paget-Blanc et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the mouse’s small size, tsDCS stimulation can be successfully delivered in normal mice [ 47 ] and in spastic mice after spinal cord injury [ 48 ], which inspired successful tsDCS stimulation testing in spastic human patients [ 49 ]. Because truly non-invasive spinal electrical stimulation had never been performed on awake ALS mice, we anticipated many technical challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Given that robotic intervention targeted more than one joint of the upper limb, the MTS was evaluated both as a summed score across 11 joints of the upper extremity, MTS total, and at the individual joint complexes for the shoulder, MTS shoulder (summed across 3 joints: horizontal adductors, vertical adductors, internal rotators), the elbow, MTS elbow (summed across 4 joints: elbow flexors, elbow extensors, pronators, supinators), and the wrist, MTS wrist (summed across 4 joints: wrist flexors, wrist extensors, fingers, palmer interrossei/flexor digitorum superficilias). For studies involving whole-limb intervention, summed scores are advantageous as they may more sensitively detect changes across trained muscles groups ( Pundik et al, 2014 ; Paget-Blanc et al, 2019 ). We selected to use the MTS instead of the Modified Ashworth Scale (MAS) as the MTS has been shown to be more sensitive to changes in spasticity ( Mehrholz et al, 2005 ; Haugh et al, 2006 ).…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that robotic therapy provides clinically significant benefits to upper limb motor recovery after stroke ( Volpe et al, 2009 ; Lo et al, 2010 ; Chang et al, 2017 ; Edwards et al, 2019 ), and can specifically reduce upper limb flexor synergy patterns through shoulder/elbow robotic training ( Dipietro et al, 2007 ). We have also demonstrated that treatment aimed at passively elicited spasticity reduction can unmask latent motor potential ( Paget-Blanc et al, 2019 ). In this study, we tested whether maximal and optimized current delivered to the auricular branch of the vagus nerve during pre-motor activity for robot-trained extensor movements would reduce spasticity and generate additional motor recovery of arm function after stroke.…”
Section: Introductionmentioning
confidence: 98%